Venom from Opisthacanthus elatus scorpion of Colombia, could bemore hemolytic and less neurotoxic than thought (2015)
We report the first biochemical, biological, pharmacological and partial proteomic characterizationstudies of the Opisthancanthus elatus venom (Gervais, 1844) from Colombia.